THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (International journal of artificial intelligence, 2025)
Author describes the experience of using ready-made neural networks (ChatGPT) and those developed by means of chat bot designers as a means of teaching Russian as a foreign language; the advantages and disadvantages of introducing chatbots in teaching business and scientific communication are revealed; the prospects for introducing artificial intelligence into the practice of teaching Russian as a foreign language are determined.